External Assessments in Special Cases - Ter-Martirosyan, Anna (Departmental Papers; Departmental Paper ;, 2014)
External Assessments in Special Cases presents the pilot External Balances Assessment methodology developed by IMF staff for estimating current account and exchange rate gaps for a group of advanced and emerging market economies, and discusses modifications to take account of special cases. Different approaches to external assessments for countries with special circumstances are evaluated, and some tools presented that could be used to inform sound judgment on the part of those conducting such assessments.